Practices in primary health care oriented toward the harmful consumption of drugs - Heloisa da Veiga Coelho; Cássia Baldini Soares
Objective To analyze the practices of primary care focused on the harmful consumption of drugs. Method This is a qualitative study, developed with a dialectical-critical approach. Data collection was carried out through semi-structured interviews with 10 employees of a basic health unit (UBS). Results The demands are not accepted, and if they go beyond the barriers shaped by the historical absence of health care practices for drug users and moralistic and preconceived ideologies, they are not reinterpreted as health needs; practices that meet these demands and go beyond the barriers are poor; the functionalist approach, which explains drug use as a disease and considers drug users as deviants, supports the few existing practices. Conclusion primary health care is mistakenly focused on addiction; it lacks structural elements of the production process in health and internal dynamics of the working processes that would foster the development of collective practices.